High-performance metal layered composite material and preparation method thereof
By using hydrogenated prealloy powder and vacuum sintering molding technology, combined with molding and cycling step heat treatment, the problems of poor compatibility and insufficient interface contact force in the preparation of metal layered composite materials are solved, and the high-performance metal layered composite materials are realized. preparation.
Patent Information
- Application Number
- CN202411653462.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-02-18
AI Technical Summary
In the preparation of metal layered composite materials, the prior art problems such as poor compatibility, insufficient interface contact force, and difficult-to-melting alloys to prepare layered composite materials, resulting in unstable material performance and low production efficiency.
The hydrogenated prealloy powder and vacuum sintering molding technology are used to achieve a firm metallurgical combination between different metal sheets through molding and cycling step heat treatment, forming a high-performance metal layered composite material.
The close bond between different metal sheets is achieved, the strong plasticity and toughness of the composite material is improved, the occurrence of defects such as edge cracks is avoided, and the comprehensive performance of the material is simultaneously improved.
Smart Images

Figure CN119457086A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of high-performance materials, and in particular relates to a high-performance metal layered composite material and a preparation method thereof. Background Art
[0002] Based on the bionic design of natural shell structures, people have developed metal layered composites. Metal layered composites are composite materials made of two or more layers of different metal materials stacked together. They have high mechanical properties, can meet the needs of aerospace and other fields for new structural materials, and have broad application prospects.
[0003] At present, the preparation of metal layered composite materials mainly comes from two or more metal materials. The compatibility between materials is crucial for the preparation of composite materials. However, due to the differences in composition, structure, organization and performance of dissimilar materials, the compatibility and interface contact force between each other are poor. In addition, it is difficult to prepare layered composite materials for refractory and difficult to form alloys. The existing technologies used include: explosive welding, hot pressing diffusion and rolling composite method. The explosive welding method not only requires special equipment and safety measures, but also requires high costs. Not all metal materials are suitable for explosive welding. The compatibility and performance differences between different materials may affect the welding effect. There are often defects or unevenness. When multi-layer composites are required, the overall production efficiency will also be greatly reduced, which greatly limits the production and application of metal layered composite materials; the hot pressing diffusion method is also very dependent on equipment and cost. In the hot pressing process, stress concentration will be introduced into the material, and defects such as Cockendall voids will be generated, which will affect the mechanical properties of the composite material. Additional post-processing processes are often required to improve the performance of the composite material, thereby increasing the complexity and cost of production; the rolling composite method is simple, but there are certain restrictions on the thickness and shape of the material, and it is difficult to achieve the molding of composite materials with complex shapes. Moreover, not all metal materials are suitable for composite rolling. The compatibility of materials and processing technology will affect the quality of the final product, especially for two refractory metal materials. Due to the incoordination and uneven deformation between the two metals, stress concentration will occur on the bonding surface, resulting in failure and fracture, which will greatly reduce the availability of the formed composite material. In addition, the temperature control during the rolling process is more difficult, and the rolling temperature of large-sized or dissimilar metal materials is even more difficult to control. Too high or too low temperature will affect the microstructure and performance of the material, causing the performance of the formed material to deteriorate.
[0004] Therefore, how to improve safety, develop new processes, reduce holes, improve the interfacial bonding strength between metal sheets, inhibit the incoordination, uneven deformation and stress concentration between metals caused by the rolling composite method when the deformation is large, effectively avoid failure and fracture, improve the compatibility, contact force and toughness of the interface area and the intermetallic compound layers of different components, regulate the content of the interface area and the intermetallic compound layer, and achieve high-performance and low-cost metal layered composite materials of both small and large sizes, dissimilar alloys, and refractory and difficult to form alloys. This is a key technical problem that needs to be solved urgently. Summary of the invention
[0005] The present invention provides a high-performance metal layered composite material, and its preparation method comprises the following steps:
[0006] (1) Place n blocks of equal size A1, A2, ...A n The surface of the metal sheet is cleaned with a degreasing cleaning agent, sandblasted, pickled, and dried for later use;
[0007] (2) Place a layer of (A1) on the A1 board y -A n )H x Hydrogenated pre-alloyed powder, put A2 plate, and then continue to lay a layer (A y -A n )H x Hydrogenate pre-alloyed powder, then add A1, A3...A n Any of the following boards, continue to lay a layer (A y -A n )Hx hydrogenated pre-alloyed powder, and then alternately stack n plates in the above manner, and evenly spread a layer of (A) between every two plates. y -A n )H x The pre-alloyed powder is hydrogenated and then pressed at 500-700 MPa to obtain A1-A n Type multi-layer composite pre-pressed blank;
[0008] (3) A1-A obtained in step (2) n The multi-layer composite pre-pressed blank is kept at 300℃-1000℃ for 1-10h; then heated to Ts+50℃ and kept for 30-60min, and subjected to 2-10 cycles of step heat treatment, and then kept at 1000-1500℃ for 1-10h, and then cooled to room temperature to obtain a high-performance metal layered composite material, wherein each step heat treatment is: kept at Ts-50℃ for 15-30min, and then kept at Ts+50℃ for 15-30min; Ts is A1, A2...A n The phase transition temperature of any combination of metals;
[0009] The n in step (1) is 2-10 and is an integer, A1, A2...A n Any combination of Ti alloy, Zr alloy, Nb alloy, Hf alloy, Ni alloy, Cr alloy, W alloy, Mo alloy, V alloy or Ta alloy;
[0010] Step (2) (A y -A n )H x The preparation method of hydrogenated pre-alloy comprises the following steps: firstly y Alloy and A n Alloy is smelted into A y -A n Alloy ingot, under hydrogen protection, A y -A n The alloy ingot is kept at 350℃ for 0.5-10h, then kept at 400℃-800℃ for 1-5h, and then cooled to room temperature to obtain (A y -A n )H x Hydrogenation pre-alloying;
[0011] The (A y -A n )H x The average particle size of the hydrogenated pre-alloyed powder is 10 to 100 μm; y Contains one of Ti, Zr, Ta or Hf alloy.
[0012] Furthermore, the surfaces of the Zr plate and the Nb plate were cleaned with a degreasing cleaning agent, sandblasted, pickled, and dried; a layer of (Zr-Nb)H x Hydrogenate the pre-alloyed powder, place a Zr plate, and then continue to lay a layer of (Zr-Nb)H x Hydrogenated pre-alloyed powder, and then placed on the Nb plate to form a two-layer Nb plate, two layers of (Zr-Nb)H x A sandwich structure consisting of hydrogenated pre-alloyed powder and a layer of Zr plate in the middle; then, the composite pre-pressed blank is obtained by compression molding at 500MPa, and the pre-pressed blank is kept at 700℃ for 3h, then at 900℃ for 30min, and then subjected to 4 cycles of step heat treatment, and then kept at 1200℃ for 2h. Finally, it is cooled to room temperature to obtain a Nb / Zr / Nb high-performance metal layered composite material. Each step heat treatment is: keeping at 800℃ for 15min, and then keeping at 900℃ for 15min.
[0013] Furthermore, the surfaces of the three TC4 plates and the two Nb521 plates were cleaned with a degreasing cleaning agent, and then sandblasted, pickled, and dried; the TC4 plate was placed at the bottom layer, and the two different plates were stacked alternately, and a layer of (TC4-Nb521)H was evenly laid between every two plates.x Hydrogenated pre-alloyed powder to form a three-layer TC4 plate, a four-layer (TC4-Nb521)H x A TC4-Nb521 alloy multilayer composite material composed of hydrogenated pre-alloyed powder and two layers of Nb521 plates is pressed at 700 MPa to form a laminated composite plate pre-pressed billet; the pre-pressed billet is kept at 800°C for 5 hours and then at 950°C for 60 minutes; then 5 cycles of step heat treatment are carried out, and then the pre-pressed billet is kept at 1300°C for 3 hours. Finally, the TC4-Nb521 high-performance metal layered composite material is obtained after being cooled to room temperature. Each step heat treatment is as follows: keeping at 850°C for 30 minutes, and then heating to 950°C and keeping for 30 minutes.
[0014] Compared with the prior art, the advantages of the present invention are as follows:
[0015] When preparing laminated composite materials by traditional hot pressing diffusion method and rolling composite method, pressure and thermal diffusion are mainly used to form effective metallurgical bonding. The metallurgical bonding strength formed by thermal diffusion is limited, which limits the application of molding materials. When the rolling composite method is pressed with a small amount, the performance of the prepared material is difficult to improve. Increasing the pressure may cause defects such as edge cracks, which makes the material unusable, and it is difficult to achieve simultaneous improvement of the strength and plasticity of the composite material. The present invention achieves a firm metallurgical bond between laminated and heterogeneous composite plates through the coordinated regulation of components, component ratios, processes and parameters, with excellent performance and no defects such as edge cracks. Its unique layered structure design reduces the sensitivity of strength to defects, overcomes the weakness of intermetallic compound materials that suddenly break due to poor toughness, and simultaneously improves the strength, plasticity and toughness of the composite material, making the contact between metal materials closer.
[0016] The present invention utilizes the hydrogen embrittlement and dehydrogenation characteristics of hydrogenated pre-alloyed powder, combined with vacuum sintering molding technology and related process parameters, to prepare heterogeneous refractory metal layered composite materials. Hydrogenated pre-alloyed powder has a characteristic different from ordinary powder, namely hydrogen embrittlement, and is very easy to break and deform. When the material structure obtained by the present invention is pressed, the multiple crushing and rearrangement of the hydrogenated pre-alloyed powder allows the pressed green sheet to form a dense structure as a whole and can avoid plastic deformation and stress concentration between large metal sheets, so that the heterogeneous metal sheets form the first combination to obtain a layered composite sheet pre-pressed green sheet; another characteristic is the dehydrogenation characteristic. When the pre-pressed green sheet is sintered, when the temperature increases to above 300°C, the hydrogenated powder will begin to dehydrogenate. In terms of macroscopic performance, the volume shrinkage caused by dehydrogenation will occur uniformly throughout the pre-pressed green sheet layer, which helps to further closely combine the heterogeneous metal sheets. In essence, the H atoms in the hydrogenated alloy powder will combine with the O atoms at the interface of the heterogeneous metal sheets to form water vapor and escape. At the same time, the tiny impurities at the heterogeneous metal bonding surface can also be taken out, which plays a purification role. In terms of microscopic performance, H atoms can stimulate the diffusion efficiency of elements in the powder-sheet interface micro-area, promote the diffusion of elements between dissimilar metal sheets, and thus promote the second metallurgical bonding between dissimilar sheets. After keeping warm in the range of 300-1000℃, the hydrogenated powder is completely dehydrogenated, and the temperature is continued to rise to Ts+50℃ (Ts alloy phase transition point temperature), and then the heating is stopped and kept warm, and then multiple heating and cooling cycles are performed in the temperature range of Ts-50℃ to Ts+50℃. The process of heating and cooling causes repeated phase change diffusion at the alloy bonding surface, promoting the re-bonding between dissimilar alloys, and this process is repeated to finally complete the preparation of multilayer composite materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 A1-A n Schematic diagram of sheet stacking;
[0018] Figure 2 Schematic diagram of the processing of high-performance metal layered composites. DETAILED DESCRIPTION
[0019] Example 1 (Preparation of (Zr-Nb)H x Hydrogenated pre-alloyed powder
[0020] Sponge zirconium and niobium particles were first smelted into Zr-Nb alloy ingots. Then, under hydrogen protection, the Zr-Nb alloy was kept at 350°C for 1 h, then at 600°C for 2 h, and then cooled to room temperature to obtain (Zr-Nb)H x Hydrogenation pre-alloying; preparation of (Zr-Nb)H by mechanical crushing and grinding x The pre-alloyed powder was hydrogenated and then sieved to obtain (Zr-Nb)H with an average particle size of 20 μm. x Hydrogenated pre-alloyed powder.
[0021] Example 2 (Preparation of (TC4-Nb521)H x Hydrogenated pre-alloyed powder)
[0022] First, TC4 alloy and Nb521 were smelted into TC4-Nb521 alloy ingots. Then, under hydrogen protection, TC4-Nb521 alloy was kept at 350℃ for 2h, then kept at 700℃ for 3h, and then cooled to room temperature to obtain (TC4-Nb521)H x Hydrogenation pre-alloying; preparation of (TC4-Nb521)H by mechanical crushing and grinding x The pre-alloyed powder was hydrogenated and then sieved to obtain (TC4-Nb521)H with an average particle size of 10 μm. x Hydrogenated pre-alloyed powder.
[0023] Example 3 (Preparation of Nb-Zr-Nb layered composite material)
[0024] The surfaces of the 1 mm Zr plate and the 1 mm Nb plate were cleaned with a degreasing agent, sandblasted, pickled, and dried. A layer of (Zr-Nb)H with a thickness of about 1 mm and an average particle size of 20 μm was laid on the Nb plate. x The hydrogenated pre-alloyed powder was placed on a Zr plate, and then a layer of (Zr-Nb)H with a thickness of about 1 mm and an average particle size of 20 μm was laid. x Hydrogenated pre-alloyed powder, and then placed on the Nb plate to form a two-layer Nb plate, two layers of (Zr-Nb)H x The sandwich structure is composed of hydrogenated pre-alloyed powder and a layer of Zr plate in the middle. The Nb / Zr / Nb composite pre-pressed billet is obtained by compression molding at 500MPa. The pre-pressed billet is kept at 700℃ for 3h, and then the temperature is increased to 900℃ for 30min. After 4 cycles of step heat treatment, the temperature is increased to 1200℃ for 2h, and finally cooled to room temperature to obtain a Nb / Zr / Nb layered composite material with a thickness of about 3mm. Each step heat treatment is: keep at 800℃ for 15min, and then increase the temperature to 900℃ for 15min.
[0025] Example 4 (Preparation of TC4-Nb521 alloy multilayer composite material)
[0026] Prepare 3 1mm TC4 plates and 2 1mm Nb521 plates, clean them with degreasing cleaning agent, sandblast, pickle and dry them. Stack the two different plates alternately (TC4 plate is placed at the bottom), and evenly spread a layer of (TC4-Nb521)H with an average particle size of about 10μm between each two plates. x Hydrogenated pre-alloyed powder to form a three-layer TC4 plate, a four-layer (TC4-Nb521)H xThe TC4-Nb521 alloy multilayer composite material composed of hydrogenated pre-alloyed powder and two layers of Nb521 plates was pressed into a laminated composite plate pre-pressed blank at 700MPa. The pre-pressed blank was kept at 800℃ for 5h, then heated to 950℃ for 60min. Then, 5 cycles of step heat treatment were performed, and then the temperature was raised to 1300℃ for 3h. Finally, after cooling to room temperature, a TC4-Nb521 alloy multilayer composite material with a thickness of about 7mm was obtained. Each step heat treatment was: keeping at 850℃ for 30min, and then heating to 950℃ for 30min.
[0027] Table 1 Process parameters and properties of multilayer composite materials obtained in Examples 3 and 4
[0028]
[0029] Table 2 Process parameters and properties of pure Nb, pure Zr and rolled Nb / Zr / Nb layered composites for industrial use in existing research
[0030]
[0031] Comparative Examples 1 and 2 in Table 2 are commercially available rolled pure Nb plates and Zr plates and their corresponding properties, while Comparative Example 3 is prepared by a traditional rolling composite method, by stacking 2 mm Nb plates and Zr plates, heating and insulating them, and then rolling them to prepare a 3 mm Nb / Zr / Nb layered composite material when the reduction is 50%. By comparing Comparative Examples 1, 2 and 3 in Table 2, it can be found that the 3 mm Nb plate, Zr plate and Nb / Zr / Nb layered composite material of the same thickness, the Nb / Zr / Nb layered material formed by the traditional rolling process, has an improved elongation compared with the two pure metal plates, but the tensile strength is lower than that of the pure Zr plate, and the improvement compared with the pure Nb plate is also limited. It can be seen that it is difficult to achieve simultaneous improvement in the elongation and strength of the composite multilayer material obtained by the prior art. When the elongation is higher than that of a single metal, the strength will be lower than that of a single metal. If the tensile strength needs to be further improved, multiple passes of large reduction rolling are required. Multiple passes of large reduction rolling not only make the process cumbersome but also lead to a decrease in the elongation or strength of the composite plate. At the same time, the material needs to be annealed each time it is rolled, and temperature control is more difficult. Excessive reduction during rolling will also lead to internal stress concentration and cracking of the material, thereby affecting the improvement of the overall mechanical properties of the material. The new process proposed in the present invention is to obtain high-performance metal layered composite materials through the coordinated regulation of plate materials, hydrogenated powders, pre-pressing, laminated composite sintering and other methods and process parameters. As shown in Example 3 in Table 1, the Nb / Zr / Nb layered composite materials of the same thickness prepared by the present invention have greatly improved elongation and tensile strength at the same time, and the comprehensive performance is better than the composite materials and raw material alloys obtained by the traditional rolling composite method. This is because compared with the rolling composite method, the plate in the present invention does not undergo large plastic deformation, and there is no large work hardening; and in the present invention, the different metal plates are more closely bonded, and multiple cycles of metallurgical bonding are carried out. The cold pressing, diffusion of high-temperature hydrogenated powder atoms and phase change diffusion promote the formation of a firm bonding surface between different metal plates, thereby greatly improving the tensile strength, plasticity and toughness of the material simultaneously. The rolling composite method mainly makes dissimilar metals contact through plastic deformation during rolling. On the one hand, the heat treatment before rolling will cause an oxide film to form on the metal surface, hindering the combination of the two and forming defects such as cracks and pores at the interface of the material; on the other hand, due to the performance differences of different plates, the compatibility is poor, and stress concentration at the interface will occur during rolling, leading to local failure. Therefore, the rolling composite method has certain requirements for the type, size and shape of the material. The process and process parameters adopted by the present invention have no restrictions on the type, size and shape of the material, and can prepare both small and large sizes and multilayer composite materials of arbitrary shapes and structures. As shown in Example 4 in Table 1, multilayer composite materials can also be prepared for TC4 and Nb521 alloys that are difficult to melt and form. Compared with traditional rolling methods, explosive composite methods, etc., the present invention has obvious advantages.
[0032] The present invention uses the coordinated regulation of components, component ratios, processes and parameters. Since the composite material obtained by the present invention needs to select relevant process parameters according to the type of raw material alloy, only within the scope of protection of the claims of the present invention can the following excellent effects be achieved: first, the brittleness of the hydrogenated pre-alloyed powder is used to form a dense structure between the heterogeneous plates during pressing, while avoiding large plastic deformation and stress concentration of the plates. Then, the dehydrogenation characteristics of the hydrogenated pre-alloyed powder at high temperature are used to make the heterogeneous plates shrink uniformly and quickly densify to form an effective metallurgical bond. Finally, the continuous heating and cooling cycle in the phase transition point temperature range promotes further bonding between the heterogeneous plates. This is because there is a high-density interlayer heterogeneous surface between the two metal heterogeneous plates, and the interface is often in a metastable state with high free energy. Therefore, when the temperature rises to above the phase transition point temperature, the defects at the interface increase, and phase change occurs at the same time. The fine interlayer metal powder will undergo a faster phase change, and the heterogeneous atoms therein have higher energy, and will migrate along the two-phase heterogeneous interface and the grain boundary inside the layer, thereby promoting the formation of a new phase. Since a specific orientation relationship is formed between the matrix and the new phase when the phase change occurs, that is, the orientation relationship of coherence and semi-coherence, the diffusion of high-energy atoms continuously promotes the nucleation and growth of the new phase between the two phase interfaces. By cyclically heating and cooling, the new phase between different heterogeneous metals continuously diffuses to both sides, thereby forming a strong metallurgical bond, and finally achieving the improvement of the comprehensive properties of the composite material such as strength, plasticity and toughness. For different alloy materials, the processing technology and parameters used are also different. Therefore, only within the scope of the claims of the present invention can a composite material with excellent comprehensive performance be achieved.
Claims
1. A high-performance metal layered composite material, the preparation method of which comprises the following steps: (1) Place n blocks of equal size A1, A2, ...A n The surface of the metal sheet is cleaned with a degreasing cleaning agent, sandblasted, pickled, and dried for later use; (2) Place a layer of (A1) on the A1 board y -A n )H x Hydrogenated pre-alloyed powder, put A2 plate, and then continue to lay a layer (A y -A n )H x Hydrogenate pre-alloyed powder, then add A1, A3...A n Any of the following boards, continue to lay a layer (A y -A n )H x Hydrogenate the pre-alloyed powder, and then complete the alternating stacking of n plates in the above manner, and evenly spread a layer of powder between every two plates (A y -A n )H x The pre-alloyed powder is hydrogenated and then pressed at 500-700 MPa to obtain A1-A n Type multi-layer composite pre-pressed blank; (3) A1-A obtained in step (2) n The multi-layer composite pre-pressed blank is kept at 300℃-1000℃ for 1-10h; then heated to Ts+50℃ and kept for 30-60min, and subjected to 2-10 cycles of step heat treatment, and then kept at 1000-1500℃ for 1-10h, and then cooled to room temperature to obtain a high-performance metal layered composite material, wherein each step heat treatment is: kept at Ts-50℃ for 15-30min, and then kept at Ts+50℃ for 15-30min; Ts is A1, A2...A n The phase transition temperature of any combination of metals; The n in step (1) is 2-10 and is an integer, A1, A2...A n Any combination of Ti alloy, Zr alloy, Nb alloy, Hf alloy, Ni alloy, Cr alloy, W alloy, Mo alloy, V alloy or Ta alloy; Step (2) (A y -A n )H x The preparation method of the hydrogenated pre-alloy comprises the following steps: firstly y Alloy and A n Alloy is smelted into A y -A n Alloy ingot, under the protection of hydrogen, y -A n The alloy ingot is kept at 350℃ for 0.5-10h, then kept at 400℃-800℃ for 1-5h, and then cooled to room temperature to obtain (A y -A n )H x Hydrogenation pre-alloying; The (A y -A n )H x The average particle size of the hydrogenated pre-alloyed powder is 10 to 100 μm; y Contains one of Ti, Zr, Ta or Hf alloy.
2. A high performance metal layered composite material according to claim 1, characterized in that: Its preparation method includes the following: The surfaces of the Zr plate and the Nb plate were cleaned with a degreasing cleaning agent, sandblasted, pickled, and dried; a layer of (Zr-Nb)H x Hydrogenate the pre-alloyed powder, place a Zr plate, and then continue to lay a layer of (Zr-Nb)H x Hydrogenated pre-alloyed powder, and then placed on the Nb plate to form a two-layer Nb plate, two layers of (Zr-Nb)H x A sandwich structure consisting of hydrogenated pre-alloyed powder and a layer of Zr plate in the middle; then, the Nb / Zr / Nb composite pre-pressed billet is obtained by compression molding at 500MPa, and the pre-pressed billet is kept at 700℃ for 3h, then at 900℃ for 30min, and then subjected to 4 cycles of step heat treatment, and then kept at 1200℃ for 2h. Finally, it is cooled to room temperature to obtain a Nb / Zr / Nb high-performance metal layered composite material. Each step heat treatment is: keeping at 800℃ for 15min, and then keeping at 900℃ for 15min.
3. A high performance metal layered composite material according to claim 1, characterized in that: Its preparation method includes the following: The surfaces of three TC4 plates and two Nb521 plates were cleaned with degreasing cleaning agent, and then sandblasted, pickled, and dried. The TC4 plate was placed at the bottom layer, and the two different plates were stacked alternately, and a layer of (TC4-Nb521) was evenly placed between every two plates. x Hydrogenated pre-alloyed powder to form a three-layer TC4 plate, a four-layer (TC4-Nb521)H x The TC4-Nb521 alloy multilayer material composed of hydrogenated pre-alloyed powder and two layers of Nb521 plates is then pressed at 700MPa to form a laminated composite plate pre-pressed billet; the pre-pressed billet is kept at 800℃ for 5h and then at 950℃ for 60min; then 5 cycles of step heat treatment are carried out, and then the pre-pressed billet is kept at 1300℃ for 3h. Finally, the TC4-Nb521 high-performance metal layered composite material is obtained after being cooled to room temperature. Each step heat treatment is as follows: keeping at 850℃ for 30min, then heating to 950℃ and keeping for 30min.